Pengaruh Profitabilitas, Pertumbuhan Perusahaan, Kebijakan Dividen dan Kepemilikan Institusional terhadap Nilai Perusahaan - Ahmad Lukman Hakim; Hijroh Rokhayati (Jurnal Riset Akuntansi Soedirman, 2026)
This study aims to analyze the effects of profitability, company growth, dividend policy, and institutional ownership on firm value in the energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The theories used in this study are signaling theory and agency theory. This is a quantitative study using secondary data. The research population includes all energy sector companies listed on the IDX between 2021 and 2024. The sample selection used a purposive sampling method, resulting in 18 companies and 72 observations. Firm value is measured using Price to Book Value (PBV), profitability is measured by Return on Equity (ROE), company growth is measured by the Asset Growth Ratio (AGR), dividend policy is measured by the Dividend Payout Ratio (DPR), and institutional ownership is measured by the percentage of share ownership by institutions. Data analysis was performed using panel data regression analysis with EViews 12. The results indicate that: (1) profitability has a positive effect on firm value; (2) asset growth of the company has a negative effect on firm value; (3) dividend policy has no effect on firm value; and (4) institutional ownership has a negative effect on firm value.